2011
DOI: 10.1016/j.ecoleng.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrated stream and wetland restoration: A watershed approach to improved water quality on the landscape

Abstract: a b s t r a c tWater quality in Upper Sandy Creek, a headwater stream for the Cape Fear River in the North Carolina Piedmont, is impaired due to high N and P concentrations, sediment load, and coliform bacteria. The creek and floodplain ecosystem had become dysfunctional due to the effects of altered storm water delivery following urban watershed development where the impervious surface reached nearly 30% in some sub-watersheds. At Duke University, an 8-ha Stream and Wetland Assessment Management Park (SWAMP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 21 publications
(29 reference statements)
2
53
0
Order By: Relevance
“…In conjunction with the loss of coarse sediments, impervious surfaces and the stripping of bank vegetation result in increased stream power and flashier stormwater runoff response, leading to an increase in erosive flows (Konrad 2013). Previous research has demonstrated that urbanisation often results in enlargement of urban channel cross-sectional area (Hession et al 2003, O'Driscoll et al 2009), incision of the stream channel and separation from the riparian zone (Groffman et al 2003, Richardson et al 2011 and lateral channel migration (Hession et al 2003, Leopold et al 2005, Wolfert and Maas 2007. In developed countries, engineering solutions are often applied to mediate the impacts of erosion in urban streams, resulting in the artificial lining of channels with concrete, rock or geomembrane materials (e.g.…”
Section: Physical/geomorphic Impactsmentioning
confidence: 99%
“…In conjunction with the loss of coarse sediments, impervious surfaces and the stripping of bank vegetation result in increased stream power and flashier stormwater runoff response, leading to an increase in erosive flows (Konrad 2013). Previous research has demonstrated that urbanisation often results in enlargement of urban channel cross-sectional area (Hession et al 2003, O'Driscoll et al 2009), incision of the stream channel and separation from the riparian zone (Groffman et al 2003, Richardson et al 2011 and lateral channel migration (Hession et al 2003, Leopold et al 2005, Wolfert and Maas 2007. In developed countries, engineering solutions are often applied to mediate the impacts of erosion in urban streams, resulting in the artificial lining of channels with concrete, rock or geomembrane materials (e.g.…”
Section: Physical/geomorphic Impactsmentioning
confidence: 99%
“…This work complements other floodplain-scale research showing that these systems have the capacity to reduce nutrients and sediment in overbank flows (Kroes et al, 2015;Richardson et al, 2011;Roley et al, 2012). The spatial and temporal variability measured here, along with questions of application in areas with potentially high legacy soil nutrients due to historic agricultural land use (Jones et al, 2015), point to a gap in the understanding of how to best apply restoration efforts for maximum water quality benefits.…”
Section: Resultsmentioning
confidence: 59%
“…In those cases, stream restoration concepts should incorporate the establishment of functional units within the stream course, which possess high nutrient uptake capacities, but often need certain maintenance activities. Examples for such functional units are in-stream sediment traps, in-stream wetlands, and slow-flowing stream reaches with planted submerged macrophytes (Filoso and Palmer 2011;Hines and Hershey 2011;Richardson et al 2011). In the USA, such functional restoration concepts involving the creation of stream-wetland complexes in lowland streams have proven to successfully increase in-stream nutrient uptake (Filoso and Palmer 2011).…”
Section: Potential and Limitations Of Mitigation Measuresmentioning
confidence: 99%